2021
DOI: 10.1016/j.jhazmat.2020.124082
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton catalysts: A review of recent advances

Abstract: Heterogeneous Fenton catalysts are emerging as excellent systems for applications related to water purification. In this review, recent trends in the synthesis and application of heterogeneous Fenton catalysts for the abatement of organic pollutants and disinfection of microorganisms are discussed. It is noted that as the complexity of cell wall increases, the resistance level towards various disinfectants increases and it requires either harsh conditions or longer exposure time for the complete disinfection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
198
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(206 citation statements)
references
References 329 publications
(419 reference statements)
1
198
0
7
Order By: Relevance
“…Over the past decade, the use of zero-valent iron was demonstrated for treating different varieties of organic and inorganic contaminants, such as dyes [ 190 ]. Thomas et al, in their recent review on heterogeneous Fenton catalysts [ 191 ], reported that zero-valent iron-based technologies have seen huge interest in both mechanistic studies and field applications for the treatment of numerous pollutants due to the environmental compatibility of iron and versatility of the process towards oxidation or reduction reactions. They believed that more applications will be seen in the future, especially if challenges on dispersibility, longevity, and reactivity control are addressed.…”
Section: Mechanism and Kinetics Of Aopsmentioning
confidence: 99%
“…Over the past decade, the use of zero-valent iron was demonstrated for treating different varieties of organic and inorganic contaminants, such as dyes [ 190 ]. Thomas et al, in their recent review on heterogeneous Fenton catalysts [ 191 ], reported that zero-valent iron-based technologies have seen huge interest in both mechanistic studies and field applications for the treatment of numerous pollutants due to the environmental compatibility of iron and versatility of the process towards oxidation or reduction reactions. They believed that more applications will be seen in the future, especially if challenges on dispersibility, longevity, and reactivity control are addressed.…”
Section: Mechanism and Kinetics Of Aopsmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs) had attracted much attention from researchers as the well‐ordered nanostructure of MOFs offers extra‐large surface area, high loading capacity well‐defined porous structure, and controllable degradation behaviors. [ 20–22 ] By selecting the appropriate organic ligands and reacting conditions, MOF structure formed on materials surface could serve as drug loading and controlled release carriers to facilitate various medical scenarios. [ 23,24 ] In particular, MOFs demonstrate tremendous potential to combat bacterial infections owing to their composition/structure associated features including responsive degradation with bacterial activity, reactive oxygen species (ROS) generation, and capability to load other antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the large-scale application of homogeneous Fenton system is typically restricted by the low operation pH range (pH = 2.5-3.5) and the generation of undesirable iron sludge (Brillas et al 2009). To minimize negative effects of homogeneous Fenton process, various heterogeneous Fenton catalysts have been developed (Nidheesh 2015, Thomas et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxides, such as goethite (Îą-FeOOH), magnetite (Fe 3 O 4 ), and hematite (Îą-Fe 2 O 3 ), are often treated as heterogeneous Fenton catalysts because of their abundance in earth crust, low cost, negligible toxicity, and environmentally benign (Thomas et al 2020). Compared with hematite and goethite, magnetite (Fe 3 O 4 ) has gain much more attention with its outstanding properties.…”
Section: Introductionmentioning
confidence: 99%